TIGA PILAR KEBIJAKAN PEMERINTAH DALAM PEMBINAAN PAUD - Istiqomah, Laelatul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
Various problems of Early childhood Education (ECD) in Indonesia is about the opportunity the acquisition of early childhood education have been uneven and is still concentrated in urban areas, lack of teachers and teaching staff in terms of quantity and quality, and there are still many learning-oriented on the wishes of the parents rather than on the needs of the child. Depart from the real conditions of the early childhood education, to lead the realization of educational system as a social institution is strong and authoritative, the government has issued the three pillars of government policy in early childhood education in the Strategic plan of the Ministry of National Education from 2009 to 2014, and now the government has fine-tune these policies in the Strategic Framework Ministry of Education and Culture of the 2014-2019 strategic plan (Strategic plan update)